Transportation Scenarios: Looking forward and looking back in four European cities - WICKHAM, JAMES JOHN RUFUS (Irish Transport Researchers Network, 2010)
The post World War II history of European urban transport in cities involves trajectories, switching points and socio-political choices. The paper contributes to our understanding of such choices by confronting the results of a scenario-building exercise carried out with urban experts in four European cities in year 2000 with subsequent developments. Already by 2000 urban experts were committed to sustainable mobility in terms of both spatial planning and transport technologies. They tended to link these aspirations to the broader European social model. However they did not expect such aspirations to be realised. Subsequent developments in the four cities show that while experts? expectations in relation to urban transport technologies were overly pessimistic, the cities have not moved significantly towards sustainable mobility and new forms of car-based mobility have emerged.
PUBLISHED
Keywords: Transport; scenarios; urban history; sustainable mobility